Strangulation of the stomach and the transverse colon following laparoscopic esophageal hiatal hernia repair - Hermann, Jacek (Termedia Publishing House, 2012)
The authors present a 32-year-old male patient with incarceration of a recurrent esophageal hiatal hernia after laparoscopic repair. A life-threatening strangulation of the stomach and the transverse colon occurred within a few days after the operation. Relapse of hiatal hernias amounts to almost half of early complications characteristic for the laparoscopic approach. General recommendations regarding surgical technique as well as perioperative care have been proposed in order to decrease the risk of relapse. Also, routine contrast radiology on the first or second day following the laparoscopic operation facilitates early diagnosis of relapse of hiatal hernia with emergent reoperation. This may result in decreased morbidity and improved overall outcome of the treatment.